2019
DOI: 10.1038/s41598-019-50757-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genes/Proteins Related to Submergence Tolerance by Transcriptome and Proteome Analyses in Soybean

Abstract: Flooding can lead to yield reduction of soybean. Therefore, identification of flooding tolerance genes has great significance in production practice. In this study, Qihuang 34, a highly-resistant variety to flooding stress, was selected for submergence treatments. Transcriptome and proteome analyses were conducted, by which twenty-two up-regulated differentially expressed genes (DEGs)/differentially expressed proteins (DEPs) associated with five KEGG pathways were isolated. The number of the DEGs/DEPs enriched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 51 publications
(59 reference statements)
4
43
0
Order By: Relevance
“…Many studies have been conducted to investigate the transcriptomes of PCgenes in response to WS condition in plants such as Arabidopsis, rice, maize, cotton, and soybean [7,9,11,69,70]. However, there are few investigations centered on lncRNAs responding to WS.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been conducted to investigate the transcriptomes of PCgenes in response to WS condition in plants such as Arabidopsis, rice, maize, cotton, and soybean [7,9,11,69,70]. However, there are few investigations centered on lncRNAs responding to WS.…”
Section: Discussionmentioning
confidence: 99%
“…The expression data was obtained from the public RNA-seq data published in Phytozome v12.1 (Libault et al, 2010;Goodstein et al, 2011). The RNA-seq data was obtained from NCBI Sequence Read Archive (SRA) with the accession number: SRP181976 (Lin et al, 2019). The expression values (Fragments per kilobase for a million reads, FPKM) for each gene were log2 transformed before generating the heatmap.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the maize trihelix genes could respond to flood stress (Du et al, 2016). Considering that many soybean trihelix genes processed the anaerobic responsive element (ARE) in their promoters, we analyzed our previous transcriptome data of the soybean cultivar Qihuang34 submerged for 3, 6, 12 and 24 hours at the seedling stage (Lin et al, 2019) (Table S6).…”
Section: The Expression Profile Of Soybean Trihelix Genes In Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Proteomic study of the soybean radicle collected from these categories showed that RNA binding/processing-related proteins and flooding stress indicator proteins correlated with flood-tolerant index [ 31 ]. Lin et al [ 105 ] reported that Qihuang 34 was a flood-tolerant cultivar, which was indicated with the highest survival ratio of seedling, and metabolic pathways relevant to carbon metabolism, mitogen-activated protein kinase signaling, fatty acid degradation, as well as isoflavonoid biosynthesis were enriched via differently changed genes and proteins under flooding. In addition, it was shown that glycolysis was activated for ATP production for plant survival; however, decreased lignin caused plant softening under submergence for a long period of time [ 105 ].…”
Section: Proteomic Analysis To Understand Flood-tolerant Mechanismmentioning
confidence: 99%